Peningkatan Motivasi dan Hasil Belajar Materi Strategi Promosi Produk Kerajinan Dengan Model Pembelajaran CIRC - Wiwit Isaroh (Faculty of Economics and Business, University of Pancasakti Tegal, 2022)
According to students, the material for promotional strategies for handicraft products from waste materials is difficult and lacking enthusiasm to learn so that motivation and learning outcomes are low, so there is a need for efforts to increase motivation and learning outcomes of students. The research objective was to determine the increase in motivation and learning outcomes as well as changes in the behavior of students in participating in learning. The implementation of classroom action research took place in 2 cycles, the results of the study showed that in cycle I and cycle II there was an increase, namely the assessment of learning motivation by 27 students (81.82%) and in cycle II as many as 31 students (93.94%), knowledge assessment in the first cycle as many as 26 students (78.78%) and in the second cycle as many as 31 students (93.94%), the skills assessment in the first cycle as many as 25 students (75.76%) and in the second cycle as many as 25 students 30 students (90.91%). Conclusion students are enthusiastic, enthusiastic, active, happy and show high motivation in following the learning and learning outcomes achieved by students have increased.